Modeling apparent camouflage-pattern color using segment-weighted spectra. Issue 5 (24th March 2019) - Ramsey, Scott; Mayo, Troy; Howells, Christopher A.; Shabaev, Andrew; Lambrakos, Samuel G.
ABSTRACT: Camouflage patterns for military applications, typically upon base materials such as dyed fabrics, consist of highly detailed camouflage patternings that are characterized by combined refectance spectra. The complexity of these camouflage patterns establishes a need for modeling camouflage-pattern reflectance for pattern evaluation as a function of distance. A metric for pattern evaluation is the apparent-camouflage-pattern reflectance spectrum, which is the total reflectance due to all contributions from component segments, within a wavelength range of interest, for light reflected from sufficiently large fabric samples (≥1m 2 ), as a function of standoff distance. This follows in that camouflage patterns tend to lose contributions to the total reflectance from component segments, having less coverage, with increasing standoff distance. Eventually, with increasing distance, reflectance of pattern segments having more coverage combine to produce the "apparent spectrum" of the camouflage pattern at far field. The physical characteristics of camouflage-pattern reflectance spectra are based on far-field and diffuse scattering properties of electromagnetic waves. Accordingly, a modeling approach can be developed to simulate camouflage-pattern spectra using diffuse-reflectance theory, which is based on decomposition of camouflage-pattern reflectance with respect to component segments of camouflage patterns. This paper presents a modeling approach and prototype simulations of camouflage-pattern reflectance within the visible range of wavelengths, which are relevant for evaluating camouflage fabrics with respect to realistic field conditions. A significant aspect of this modeling approach is that it can be extended for simulation of a wide range of factors influencing detection of camouflaged targets.